Child Support - Support Whom? - Atkin, Bill; Black, Andrew (Victoria University of Wellington Law Review, 1999)
The Child Support Act 1991 has been a highly controversial piece of legislation. While much of the public consternation has quietened, questions should still be asked about the scheme. To what extent are children and caregivers gaining anything substantial? Given the State's vested interest in recouping for itself some of the cost of social security benefits, whom does child support really support? The authors note the dearth of research on the effectiveness of the scheme in achieving its goals. This article also discusses the narrow views of parental and financial responsibility enshrined in the Act and reinforced by unduly restrictive Court of Appeal rulings.